Endothelin-1 inhibits outward potassium currents in mouse outer sulcus cells - Luo, Y.; Tang, Y.; Liu, J.; Chen, Y.; Xia, Q. (Cellular and Molecular Biology, 2007)
The outer sulcus cells are epithelial cells covering the luminal side of spiral sulcus of cochlea. It has been suggested that outer sulcus cells contribute to cation absorption from the lumen of the cochlea. We investigated the electrical properties and the effects of endothelin-1 (ET-1) on the outward potassium currents in mouse outer sulcus cells using a whole-cell patch clamp technique. The cell capacitance was 3.16+/-0.66 pF (n =35) and the resting membrane potential was -98.4+/-1.6 mV (n=6) in extracellular fluid bath solution. The outward K+ currents were activated by depolarizing pulses more positive than -60 mV, and was sensitive to TEA (10 mM). Tail current analysis revealed that it was primarily K+ selective. Application of ET-1 caused a decrease of outward potassium currents within seconds, whereas treatment with BQ123, a competitive inhibitor of the ET type-A receptor, counteracted the inhibitory effect of ET-1. These results suggest that ET-1 inhibits outward potassium currents through the activation of ET type-A receptor. ET-1 may play an important role in maintaining the ionic homeostasis of endolymph.